Peran Pembina Pramuka dalam Menanamkan Kepedulian Sosial Siswa di MTsN 2 Bondowoso Tahun 2019 - Junaedi Muhammad (Institut Agama Islam Negeri Jember, 2021)
Instilling social awareness is an important thing to be instilled in students to foster feelings and behavior of caring for others. Instilling social awareness through scout extracurricular activities at MTsN 2 Bondowoso has an important role in developing positive attitudes, leadership characters and caring for others. This research is a qualitative research and the type of research is descriptive. Data collection techniques using non-participant observation techniques, interviews and documentation. Analysis of the data using the interactive model of Miles and Huberman. The validity of using triangulation of sources and techniques. The results of this study are: 1). inculcating student social awareness; (a) through habituation such as greeting each other, say hello, pay infaq, do charity work and pray for a sick friend; (b) training activities such as, work together and help each other in pioneering, setting up a tent and simulating First Aid In Accident; (c) work programs such as: social services, sowing flowers, raising funds for victims of natural disasters and distributing 1000 zakat; 2) supporting factors for inculcating student social awareness, that is: (a) the existence of scout coaches who can guide and teach about manners to students with mutual respect and help each other; (b) the presence of a teacher, who provides direction and motivation to students; (c) the role of parents who give permission to their children in participating in scouting activities and participating in material matters